Role of Credit Management Analysis to Reduce the Occurrence of Problem Loans (Study on People’s Credit Bank in Gianyar District) - Sari, Ni Made Taman; Santini, Ni Made; Dewi, Made Pratiwi (International Journal Of Management And Economics Invention, 2022)
This study aims to identify and analyze credit management, the causes of bad credit, and the handling of loan problems in banking. This study uses quantitative methods and the data used are secondary data. The data used is based on the application of credit management and credit collectability data, the level of Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), loan limit and Loan to Deposit Ratio (LDR). The results of this study indicate that Rural Banks have carried out the stages of credit management appropriately. The findings in this study indicate that the causes of bad loans are debtors who have family problems, business failures, job terminations and the covid 19 pandemic disaster. Non-performing loans are handled by rescheduling.